Quality of life and symptom burden among myeloproliferative neoplasm patients: do symptoms impact quality of life?. Issue 2 (28th January 2019) - Langlais, Blake T.; Geyer, Holly; Scherber, Robyn; Mesa, Ruben A.; Dueck, Amylou C.
Abstract: Patients with myeloproliferative neoplasms (MPNs) are faced with high disease-related symptom burden and quality of life (QoL) decrements. This analysis assesses the extent to which individual symptoms or summary measures across symptoms impact QoL overall and within MPN subgroups. Four sets of summary measures were constructed assessing symptom prevalence and severity within group-standardized and patient-individualized approaches. Among 1416 international patients with MPNs, mean symptom severity and prevalence were highly correlated ( p < .001). Individual symptoms most impacting QoL were inactivity ( R 2 =0.29), fatigue ( R 2 =0.23), and depression ( R 2 =0.23). Multiple symptom severity scores are needed to best predict QoL. Symptom severity at the patient-level is more predictive of QoL than severity at the group-level where a fewer number of symptoms are considered. Having at least one severe symptom and having multiple symptoms of moderate intensity are meaningfully predictive of QoL decrements. Results were highly consistent across disease subgroups.